2015
DOI: 10.1002/pssb.201451581
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characteristics of a‐plane low‐Mg‐doped p‐GaN Schottky contacts

Abstract: Electrical characteristics of a variety of Schottky contacts formed with ten metal species on the a-plane of p-type lowMg-doped GaN grown on r-plane sapphire substrates were studied. We found that while current-voltage characteristics obtained under voltage scanning show no memory effect in samples formed on a-plane samples on c-plane showed a substantial memory effects. We consider that the absence of memory effect in the a-plane p-GaN samples is originating from a smaller density of interfacial defect than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…High-temperature isothermal capacitance transient spectroscopy measurements revealed that the memory effect originated from acceptor-type defects of Ga vacancies (Ev + 1.1 eV) and that these defects were localized near the p-GaN surface (21). We also found less metal-workfunction dependence due to strong surface Fermi-level pinning (22), and large surface-orientation dependences between Ga-polarization c-plane, N-polarization c-plane, and a-plane p-GaN (23,24). Recently, as the power switching electron devices have become more complicated structures like Si power devices in order to realize an e-mode operation, metal/p-GaN interfaces have been studied again for the development of lateral junction FETs and vertical transistors (25)(26)(27).…”
Section: Large-barrier P-gan Schottky Contacts By Reducing Mg Doping ...mentioning
confidence: 70%
“…High-temperature isothermal capacitance transient spectroscopy measurements revealed that the memory effect originated from acceptor-type defects of Ga vacancies (Ev + 1.1 eV) and that these defects were localized near the p-GaN surface (21). We also found less metal-workfunction dependence due to strong surface Fermi-level pinning (22), and large surface-orientation dependences between Ga-polarization c-plane, N-polarization c-plane, and a-plane p-GaN (23,24). Recently, as the power switching electron devices have become more complicated structures like Si power devices in order to realize an e-mode operation, metal/p-GaN interfaces have been studied again for the development of lateral junction FETs and vertical transistors (25)(26)(27).…”
Section: Large-barrier P-gan Schottky Contacts By Reducing Mg Doping ...mentioning
confidence: 70%